Controlling equine influenza: traditional to next generation serological assays - Kinsley, Rebecca; Scott, Simon D.; Daly, Janet M. (Elsevier, 2016)
Serological assays provide an indirect route for the recognition of infectious agents via the detection of antibodies against the infectious agent of interest within serum. Serological assays for equine influenza A virus can be applied for different purposes: diagnosing infections; subtyping isolates; surveillance of circulating strains; and to evaluate the efficacy of vaccines before they reach the market. Haemagglutination inhibition (HI) and single radial haemolysis (SRH) assays are most commonly used in the equine field. This review outlines how both these assays together with virus neutralization (VN) and ELISA are performed, interpreted and applied for the control of equine influenza, giving the limitations and advantages of each. The pseudotyped virus neutralization assay (PVNA) is also discussed as a promising prospect for the future of equine influenza virus serology.